Assessing the Use of Cohesive Devices in Reading Texts of English Textbook - Alifia Junita Cendraa Sari; Januarius Mujiyanto; Dwi Rukmini (English Education Journal, 2022)
The present study began with wide use of a textbook entitled "Bahasa Inggris" in Sorong. The book is written by Utami Widiati, Zuliati Rohmah, and Furaidah. It focuses on analyzing all the reading passages in the chosen chapters. Qualitative descriptive implemented in assessing the use of cohesive devices proposed by Halliday and Hasan’s (1976) theory. The findings reveal 895 grammatical and 222 lexical cohesions in the reading passages. The grammatical consisted of 622 references, 15 substitutions, 22 ellipses, and 236 conjunctions and the lexical cohesion consisted of 186 reiterations and 36 collocations. Furthermore, as support in providing the text's coherence, the researchers asked the students as ttextbook users to read the passages. It was proven that the texts were readable and understood by the readers. However, they took time to understand the passages with more ellipsis and collocation. Hopefully, this study will give the readers and authors insight of the reading texts by using appropriate cohesive devices in creating coherent reading texts as instruments for teaching and learning.